SAT0529 Relationship between Changes in Serum Urate and Bone Mineral Density during Treatment with Thiazide Diuretics: Secondary Analysis from A Randomised Controlled Trial. (10th June 2014) - Dalbeth, N.; Gamble, G.D.; Horne, A.; Reid, I.R.
Abstract : Background: Recent observational studies have reported that serum urate (SU) concentrations positively correlate with bone mineral density (BMD), and that higher SU concentrations are associated with reduced risk of fractures. Thiazide diuretics slow bone loss in healthy older adults, and have been associated with reduced incidence of fracture. These agents also increase SU concentrations. We hypothesized that changes in SU concentrations predict changes in BMD during treatment with thiazide diuretics. Objectives: To examine the relationship between change in SU and change in BMD during treatment with thiazide diuretics. Methods: We analysed data from a two-year double-blind randomised controlled trial of hydrochlorothiazide (50mg per day) and placebo in normal post-menopausal women 1 . The relationship between change in SU and BMD after two years of treatment was examined using Spearman correlation and linear regression models (n=124 participants). Results: After two years, total body BMD increased in the hydrochlorothiazide group by 0.0056g/cm 2 and reduced in the placebo group by 0.0032g/cm 2 (between group difference P=0.0034). SU concentration increased in the hydrochlorothiazide group by 0.036mmol/L and reduced in the placebo group by 0.0059mmol/L (between group difference P<0.0001). There was no relationship between the change in total body BMD and change in SU concentration (for entire study population, r=0.13; for hydrochlorothiazide group, r=0.03; and for placebo group, r=-0.005; P≥0.13 for all). There was no difference in the regression line slopes for change in total body BMD and change in SU in the thiazide and placebo groups (Pcompare slopes =0.997). In multiple linear regression models, the effects of hydrochlorothiazide on total body BMD persisted after including baseline SU and change in SU in the model (Ptreatment =0.01), with no independent influence of change in SU (Pchange in SU =0.96). Similar results were observed for BMD at individual sites (legs, mid-forearm, ultradistal forearm, lumbar spine and femoral neck). Conclusions: The effects of hydrochlorothiazide on BMD occur independently of the effects on SU concentrations. References: Reid IR, Ames RW, Orr-Walker BJ, et al. Hydrochlorothiazide reduces loss of cortical bone in normal postmenopausal women: a randomized controlled trial. Am J Med 2000;109:362-70. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3395